Impact of pre-angioplasty antithrombotic therapy administration on coronary reperfusion in ST-segment elevation myocardial infarction: Does time matter?. (15th February 2021) - Giralt, Teresa; Ribas, Núria; Freixa, Xavier; Sabaté, Manel; Caldentey, Guillem; Tizón-Marcos, Helena; Carrillo, Xavier; García-Picart, Joan; Lidón, Rosa Maria; Cárdenas, Mérida; Pérez-Fernández, Silvia; Mauri, Josepa; et al.
Abstract: Background: Optimal timing of antithrombotic therapy for patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) is unclear. We analyzed the impact of pre-angioplasty administration of unfractionated heparin (UFH) on infarct-related artery (IRA) patency and mortality. Method: Multicenter prospective observational study of 3520 STEMI patients treated with PPCI from 2016 to 2018. Subjects were divided into four groups according to the elapsed time from heparin administration to PPCI: Group 1: Upon arrival at catheterization laboratory or ≤ 30 min ( n  = 800; 22.7%); Group 2: 31 to 60 min ( n  = 994; 28.2%); Group 3: 61 to 90 min ( n  = 1091; 31%); Group 4: >90 min ( n  = 635; 18%). IRA patency was defined as thrombolysis in myocardial infarction (TIMI) flow grade 2–3. Multivariate analyses assessed factors associated with IRA patency and both 30-day and 1-year mortality. Results: UFH administration at STEMI diagnosis was an independent predictor of IRA patency especially when administered more than 60 min before the PPCI (OR 1.43; 95% CI 1.14–1.81), either an independent predictor of 30-day (HR 0.63; 95% CI 0.42–0.94) and 1-year (HR 0.57; 95% CI 0.41–0.80) mortality. The effect of UFH on IRA patency was higher when administered earlier from the symptom onset. Conclusion: UFH administration at STEMI diagnosis improves coronary reperfusion prior to PPCI and this benefit seems associated with superior clinical outcomes. The presented results highlight a time-dependent effectiveness of UFH, since its reported effect is greater the sooner UFH is administered after symptom onset. Highlights: Association between early pre-angioplasty UFH administration in STEMI patients and IRA patency and mortality were evaluated. UFH administration at STEMI diagnosis before PPCI improved pre-angioplasty coronary patency. This effect was greater the sooner UFH was administered after symptoms onset. UFH administration can be associated with decreased 30-day and 1-year mortality due to an earlier coronary reperfusion. Combining UFH with novel P2Y12 inhibitors did not increase the rate of reperfusion before PPCI.